2000
DOI: 10.1117/12.387616
|View full text |Cite
|
Sign up to set email alerts
|

<title>Contrast enhancement and segmentation of ultrasound images: a statistical method</title>

Abstract: Ultrasound B-scan images often exhibit intensity inhomogeneities caused by non-uniform beam attenuation within the body. These cause major problems for image analysis, both by manual and computer-aided techniques, particularly the computation of quantitative measurements. We present a statistical model that exploits knowledge of tissue properties and intensity inhomogeneities in ultrasound for simultaneous contrast enhancement and image segmentation. The underlying model was originally proposed for correction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…This may be attributed to the very noisy nature of these sequences. This comparison is limited and given to show the differences between the proposed method and pure Graph Cut algorithms, as there are some fundamental similarities such as pixel dependencies; similar to the methods described in [6,7,[9][10][11], the Graph Cut method uses MRF for this. However, more complex methods share many similarities with our method, e.g.…”
Section: Comparison With Graph Cut Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be attributed to the very noisy nature of these sequences. This comparison is limited and given to show the differences between the proposed method and pure Graph Cut algorithms, as there are some fundamental similarities such as pixel dependencies; similar to the methods described in [6,7,[9][10][11], the Graph Cut method uses MRF for this. However, more complex methods share many similarities with our method, e.g.…”
Section: Comparison With Graph Cut Methodsmentioning
confidence: 99%
“…A similar approach is employed in [6][7][8][9][10], where Markov random field (MRF) regularization is used. Like our model, in [7,[9][10][11] a Bayesian framework is used, although the construction of the posterior density function is different. Our approach uses priors on location and shape; of the forementioned, only one work [9] uses a shape prior.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that sonography is superior to mammography in two aspects: (1) its ability to detect focal abnormalities in the dense breasts of adolescent women [22]; and (2) the fact that ultrasound images are acquired with a relatively lower health risk to the patient, and at a lower cost [25]. Sonography is an important adjunct to mammography in breast cancer detection and has been especially useful in distinguishing cysts from solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes, the edges of the breast tissue and masses were blurry, the contrast was low and the masses usually could not be well analyzed. In addition, it has a limitation in detecting microcalcifications (Xiao et al 2000). With the development of computer applications, many imaging tools based on computer-aided diagnosis (CAD) technologies were developed to enhance the physician's diagnostic accuracy.…”
Section: Introduction and Literaturementioning
confidence: 99%